A Proposal for a New Administrative-Territorial Outline of Bucharest-Based in-City Discontinuities - Radu Săgeată (Transylvanian Review of Administrative Sciences, 2019)
Urban development represents a permanent challenge for space organization in large cities. Space organization is to be achieved by observing the homogeneity and specificity of dwelling cores (urban quarters) as premises for urban structure functionality and viability. The administrative boundaries should overlap discontinuity areas in the city, which cause divergent population flows. The radial-concentric type morphostructure of Bucharest, Romania’s capital-city, is based on the sectorial model of six administrative sectors, in this case. Each sector has both central and peripheral zones, with sharper inter-sectorial than intra-sectorial disparities. Massive industrialization and urbanization in the socialist period led to the development of the housing stock and the individualization of quarter centers as secondary polarization cores in the city. This situation calls for revisiting the current administrative boundaries in the light of city discontinuities and establishing some multicore sectors by encompassing homogeneous quarters in terms of functionality, specificity, and social-urbanistic problems, so that administrative and local development policies could better match the concrete situations on the ground.